Differences In The Effect Of Mineral Water On The Pulse Rate Of The 400-Meter Running Experiment - Emelda, Yulia; Wati, Isti Dwi Puspita; Quinto, Janna Marie B. (CV Media Inti Teknologi, 2025)
This research is an experimental descriptive research. The research was conducted with the aim of obtaining data on pulse rate differences in the 2nd set. This study uses a sample of active students of the Department of Sports Coaching Education, class of 2021 totaling 9 people. The results showed that the sample tried to run 400 x 3 with as many as 2 attempts. The data was analyzed by descriptive and differential tests. The results of the study proved that the difference in the pulse rate of the first set was 157.33 beats per minute while the pulse rate of the second set was 166 beats per minute. It can be seen that the difference between the first and second set pulse rates is higher than the second set pulse rate. The lowest minimum score is the first set pulse rate of 132, while the second set pulse rate is 138. So that the data from the first and second sets of pulse rate difference test results are different. The conclusion in this study is the difference between the first set of pulse < the second pulse. (166.00 < 157.33) the pulse of the first set and the pulse of the second set.